DECODING YAP-DRIVEN MALIGNANT REPROGRAMMING IN ORAL EPITHELIAL STEM CELLS THROUGH SINGLE-CELL ANALYSIS - Harmin; Putri, Indah Salsabila Febriana; Maharani, Hanisa Aulia (Journal of Stem Cell Research and Tissue Engineering, 2025)
Oral squamous cell carcinoma (OSCC), a major subtype of head and neck squamous cell carcinoma (HNSC), is characterized by high mortality rates and cellular heterogeneity that complicates early detection and treatment. Recent advances in cancer biology suggest that tumorigenesis involves reprogramming of epithelial progenitor cells into cancer stem-like cells (CSCs), driven by oncogenic signaling such as Yes-associated protein (YAP) activation. YAP, a key effector of the Hippo pathway, regulates transcriptional programs involved in cell proliferation, dedifferentiation, and inhibition of differentiation. However, the specific mechanisms by which YAP reprograms oral epithelial stem cells remain incompletely understood. This literature review systematically explores findings from studies published between 2020 and 2025 that investigate the role of YAP in malignant reprogramming, particularly through single-cell analysis approaches. Articles were sourced from PubMed and Google Scholar using defined inclusion criteria, focusing on original studies involving in vitro, in vivo, or bioinformatic models. The review highlights that YAP activation in oral epithelial cells induces stemness-associated genes (e.g., SOX2, NANOG, OCT4), represses differentiation pathways (Notch, p63), and promotes epithelial-mesenchymal transition (EMT) markers (ZEB1, SNAI2, VIM). Single-cell RNA sequencing (scRNA-seq) has revealed dynamic and hybrid cell states, supporting the view that YAP-driven transformation is gradual and reversible. YAP also shapes the tumor microenvironment by inducing cytokines that recruit tumor-supportive immune and stromal cells. Key YAP-regulated targets such as CTGF, AXL, and ITGA6 emerge as potential therapeutic entry points, as their inhibition reduces proliferation and stemness. These findings underscore YAP’s central role in oral carcinogenesis and its promise as a molecular target for early intervention and therapy.